Antecedents Affecting Customer Satisfaction Hirotoland Bogor City Branch - Nida Rifnida; Christina Ekawati (Jurnal Indonesia Sosial Teknologi, 2023)
This study aims to analyze the influence of differentiation strategy, service quality, and promotion on customer satisfaction at Hirotoland Branch Bogor. The sample used in this study consisted of 100 individuals. The data analysis method employed was multiple linear regression. The results of hypothesis testing simultaneously indicate that the variables of differentiation strategy, service quality, and promotion significantly affect customer satisfaction. The results of partial hypothesis testing show that each variable, namely differentiation strategy, service quality, and promotion, significantly influences customer satisfaction. This research contributes to the understanding of factors affecting customer satisfaction at Hirotoland Branch Bogor and provides insights for management to develop more effective strategies to enhance customer satisfaction.